O Direito Fundamental à Liberdade Cognitiva: Autonomia mental, cultura e poder na era da manipulação algorítmica - Maestri, Letícia de Almeida (2025)
This dissertation investigates the fundamental right to cognitive freedom in the digital age, analyzing how algorithmic manipulation, the attention economy, and neurotechnologies affect mental autonomy, culture, and power relations. The study seeks to understand how these elements shape the dynamics of digital imperialism, concentrating the flow of information, conditioning collective thought, restricting cultural diversity, and limiting individuals' capacity for self-determination. The first chapter discusses the philosophical and historical foundations of cognitive freedom, linking it to the relationships between cognition, culture, and domination. It argues that cognitive freedom is not merely the absence of coercion but materializes in the transformation of institutions and the expansion of the public sphere, making it a space conducive to dialogue, resistance, and social change. Additionally, it highlights that culture is not a neutral field but a symbolic battleground that can be instrumentalized as a tool of control. The second chapter examines how algorithms, under the false promise of neutrality, reconfigure power relations by controlling the circulation of information and concealing content that escapes dominant market and political logics. It discusses the impact of the attention economy and cognitive standardization, exposing the effects of excessive exposure to digital stimuli on mental health and the development of neurodamage, such as anxiety, attention deficit, and burnout. It also explores how digital imperialism, structured by large technology corporations, imposes a hegemonic cultural model, reducing thought diversity and hindering the construction of alternative and counter-hegemonic narratives. The third chapter proposes a new legal and ethical paradigm to protect cognitive freedom in the digital age. It argues for the regulation of algorithmic transparency, informational self-determination, and protection against behavioral manipulation, along with the strengthening of digital sovereignty as a defense against the concentration of informational power in the hands of a few corporations. The dissertation underscores the urgency of a legal approach that considers culture and power relations, ensuring that the protection of cognitive freedom is not limited to the individual sphere but rather a collective project of resistance against digital colonialism. The dissertation concludes that cognitive freedom is under threat, requiring a legal and political response to combat the effects of digital imperialism and promote the democratization of information. It proposes effective regulation of algorithms, accountability for Big Tech companies, digital sovereignty, and critical digital education as essential measures to preserve mental autonomy, democracy, and ensure cultural diversity in the digital space. Finally, it defends the idea that true subject emancipation—and, consequently, social transformation—depends on overcoming structures that restrict critical thinking and on building a digital environment that values plurality and citizens' self-determination.